KERANGKA EPISTEMOLOGI (Metode Rekonstruksi Pendidikan Agama Islam) - Moh. Elman; Mahrus Mahrus (Rabbani: Jurnal Pendidikan Agama Islam, 2020)
ABSTRACTThe epistemology of Islamic education study is an attempt to dismantle the studies that are in it, both essentially, methods, foundation, source, and validity of this Islamic education. Islamic education is a conscious effort in forming perfect individuals, namely individuals who are able to live their lives in an Islamic way. Discussion in Islamic education has three aspects, namely, aspects of faith, creed, and worship. With such a realm of morality, ethics and morals will become a major thing in Islamic education. Therefore the scope of the discussion of Islamic education is more likely to develop in accordance with the era, to make education as a balance against the development of the era by originating in faith and piety as a fundamental mentality in Islam itself. ABSTRAKKajian epistemologi pendidikan Islam merupakan sebuah usaha dalam membongkar kajian-kajian yang ada didalamnya, baik secara hakekat, metode, landasan, sumber, dan validitas pendidikan agama Islam ini. Pendidikan Islam merupakan usaha sadar dalam membentuk individu yang sempurna, yaitu individu yang mampu menjalani kehidupannya secara Islami. Bahasan dalam pendidikan Islam mempunyai tiga aspek. yaitu, aspek keimanan, akidah, dan ibadah. Dengan seperti itu ranah akhlak, etika dan moral akan menjadi suatu hal yang utama dalam pendidikan Islam. Jadi, ruang lingkup bahasan pendidikan Islam lebih dimungkinkan berkembang sesuai dengan perkembangan zaman, hingga menjadikan pendidikan sebagai pengeimbangan terhadap perkembangan zaman tersebut dengan bersumber pada iman dan takwa sebagai mental fundamental dalam Islam sendiri.